Fatigue Life Comparison of Modified and Conventional 3 Leg Jacket Offshore Structure - Murdjito Murdjito; Muhammad Nabil Ghiffary; Rudi Walujo Prastianto (Department of Ocean Engineering, 2020)
The jacket structure must be adapted to the conditions of the production field to support economic factors. So, the concept of a modular platform for minimal, low-cost facilities is adopted. However, the design differences will affect the performance of the jacket itself, in other words a modular jacket can withstand the same load as a conventional jacket model but has a different structural performance. Therefore, this research discusses the performance comparison, which includes the fatigue life and the natural period, between conventional and modular jacket structures, which in this study are referred to as modified jackets. Conventional jacket as a comparison structure takes the design basis of the modified structure, including the same structural profiles, and environmental loads. In this study, the two jackets will only be modeled on the jacket part and the superstructure will be modeled as a joint load on the three upper ends of the jacket legs. Fatigue life analysis in this study used the full spectral analysis method. By using SACS software, the natural period of modified jacket is 1.756 s and conventional jacket is 1.472 s. While the lowest fatigue life on modified jacket is 44.98 years and conventional jacket is 9125.79 years.